We all love X. But why? - Justice, Emma (New Statesman, 1996)
The writer discusses the success of the American television mystery drama series The X-Files. She explores the concept of the series, which involves two FBI special agents investigating unexplained FBI cases known as X-files; some plotlines; the phenomenon that the series has generated; the fans; and the commercial spin-offs. In addition, critical appraisal from four commentators and slogans that have become identified with the series are outlined.